(untitled) (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2024)
Rhampholeon acuminatus is a critically endangered species in Tanzania's Nguru Mountains. Its main threat is habitat loss due to human activities like farming and the pet trade. Understanding public awareness and perceptions about its conservation is crucial for the survival of this chameleon and other reptiles in the area. This study was conducted in five villages bordering the Mkingu Nature Forest Reserve (MNFR), part of the Nguru Mountains. This study assessed the communities’ knowledge, perception, and practices towards conserving R. acuminatus. The results revealed that 31.5% of people perceived no benefits that communities get from the preservation of R. acuminatus p = 0.001. Moreover, about 25.2% of the respondents are unaware of the activities that threaten the conservation of R. acuminatus in Nguru mountains p = 0.148. The study also found that about 88.3% of the respondents cleared the land to create space for the cultivation of crops such as cardamom, cassava, beans, and maize. The majority of the respondents (97%) reported that there are no education programs or initiatives in place that target to increase awareness of the R. acuminatus Nguru mountains, thus making it difficult for communities to identify the species. Thus, only a few respondents were able to identify the R. acuminatus during the survey, and the rest were not able to identify it even after being shown a photo p = 0.139. Thus, the study recommends public awareness programs and conservation education as well as the reduction of forest-dependent activities that target chameleon species to ensure their survival and reduce perceived threats by dispelling myths and encouraging interest in reptiles’ conservation.